Alpha- and gamma-mangostins exhibit anti-acne activities via multiple mechanisms. (3rd September 2018) - Xu, Nuo; Deng, Wenjuan; He, Gaiying; Gan, Xiaoshuang; Gao, Shuang; Chen, Yu; Gao, Yitian; Xu, Ke; Qi, Junmei; Lin, Haojie; Shen, Li; Li, Xiaokun; et al.
Abstract: Objective: Acne is a chronic skin disease that involves four key pathogenic factors: excess sebum production, ductal epidermal hyperproliferation, Propionibacterium acnes ( P. acnes ) colonization, and skin inflammation. Mangostins are well-known for their anti-bacterial and anti-inflammatory effects, suggesting that mangostins may have therapeutic potential for acne. The present study aimed to explore the anti-acne effects of mangostins from the perspective of multiple pathogenic mechanisms of acne. Methods: The effects of α - and γ -mangostins on the growth of P. acnes and lipase activity were analyzed. Their effects on P. acnes -induced keratinocyte proliferation were examined by CCK-8. The expression of inflammatory genes and activation of NF- κ B and MAPK signaling pathways were detected by quantitative real-time PCR and western blotting, respectively. Results: Alpha- and γ -mangostins not only inhibited the growth of P. acnes, but also reduced the proliferation of keratinocytes induced by heat-killed P. acnes . Furthermore, α - and γ -mangostins were able to suppress P. acnes -induced expression of pro-inflammatory cytokines, including TNF- α, IL-1 β, and IL-6 in keratinocytes by inhibiting the activation of NF- κ B and MAPK signaling pathways. Discussion and conclusions: Mangostins appeared to possess multiple anti-acne activities, including the inhibition of P. acnes growth, regulation of keratinocytes proliferation, and attenuation of skin inflammatory reaction. Hence, mangostins might be developed into a potential therapeutic agent for the treatment of acne.